Theory and Misbehavior of First-Price Auctions - Harrison, Glenn W. (American Economic Review, 1989)
Recent experimental evidence appears to reject simple Nash Equilibrium models of bidding behavior in First-Price auctions. We present a methodological critique of this evidence. Existing tests have concentrated on deviations of subjects from predictions in the message space of the auction: bid deviations. We suggest that it is more natural to evaluate subject behavior in expected payoff space. We conclude that the evidence against the simple models is not significant enough to warrant their rejection.